Advances in Flexible Optoelectronics Based on Chemical Vapor Deposition‐Grown Graphene. (15th June 2022) - Du, Jinhong; Tong, Bo; Yuan, Shuangdeng; Dai, Nian; Liu, Rui; Zhang, Dingdong; Cheng, Hui‐Ming; Ren, Wencai
Abstract: Graphene shows great potential for flexible optoelectronic devices owing to its unique 2D structure and excellent electronic, optical, and mechanical properties. Chemical vapor deposition (CVD) is the most promising method for fabricating large‐area and high‐quality graphene films at an acceptable cost; therefore enormous efforts have been attempted to investigate the flexible optoelectronic devices based on CVD‐grown graphene. Here, recent advances and significant development of CVD‐grown graphene towards flexible optoelectronics including photodetectors, organic solar cells, and light‐emitting diodes are reviewed. Insight into the challenges of improvement of optoelectronic properties, work function tuning, as well as interfacial control of CVD‐grown graphene for high‐performance devices is provided. In particular, the availability to fabricate large‐area devices on the flexible substrates is discussed, which is crucial to drive the practical use of CVD‐grown graphene for future wearable optoelectronics. Abstract : Recent advances and significant developments of chemical vapor deposition (CVD)‐grown graphene toward flexible optoelectronics are comprehensively reviewed. The challenges of improvement of optoelectronic properties, work function tuning, as well as interfacial control of CVD‐grown graphene for large‐area optoelectronic devices are discussed. Various prototype devices are demonstrated, showing great potential for CVD‐grown graphene in wearable optoelectronics.